(untitled) (Latakia University Journal -Biological Sciences Series, 2016)
نُفذ البحث في حقول محطة بحوث سيانو التابعة للهيئة العامَّة للبحوث العلميَّة الزراعيَّة في اللاذقيَّة, حيث تمَّ تقويم حساسيَّة ست سلالات من الذُّرة الصَّفراء Zea mays. L والهُجُن الخمسة عشر الناتجة باستخدام التهجين نصف التبادلي, للإصابة بحَفار ساق الذُّرة الكبير Sesamia cretica Led. تحت ظروف العَدوى الصناعيَّة وفق تصميم القطاعات العشوائيَّة الكاملة. أبدت السُّلالة IL.257-09(P1) قُدرة عامة عاليَّة لصفات عَدد الحُبُوب بالصَّف(3.089) وأعداد الثُقوب (-1.261). كما أبدت السُّلالة IL.298-09 (P2) قُدرة عامة عاليَّة لصفات طول العرنُوس(0.717), شدة الضَّرر(0.432-), النسبة المئوية لفقد الغلَّة-6.022) ). وأبدت السُّلالة IL.286-09 (P3) قُدرة عامة عاليَّة لصفات قَطر العرنُوس(0.292), عَدد الصُّفوف بالعرنُوس ((2.806. في حين أبدت السُّلالتين IL.255-09 (P4)(0.036) و IL.228-09 (P5) (0.969) قُدرة عامة عاليَّة لصفة الغلَّة الحبيَّة. وأبدت السُّلالة IL.262-09 (P6) قُدرة عامة عاليَّة لصفات وزن 100 حبّة(1.942) , الغلَّة الحبيَّة المصابة ((0.784, طول النَفق(-5.629) , النسبة المئوية لمَوت القمَّة الناميَّة-1.132) ) . كما أظهرت القُدرة الخاصَّة على الائتلاف تأثيرات عاليَّة المعنوية ومرغوبة حيث: تمَّيز الهجين (P2×P1) بقُدرة خاصَّة عاليَّة المعنوية لصفة مَوت القمَّة الناميَّة ((-0.449 وشدة الضَّرر-0.563)) وأعداد الثُقوب (-1.644) والنسبة المئويَّة لفقد الغلَّة(-2.781) . كما تمَّيز الهجين (P1×P3) بقُدرة خاصَّة عاليَّة المعنوية لصفة طول العرنوس1.368) ), الغلَّة الحبيَّة (0.050). إنّ الهجين (P6×P2) لديه قُدرة خاصَّة عاليَّة المعنوية لصفات: عَدد الصُّفوف بالعرنُوس(2.550), مَوت القمَّة الناميَّة -0.382)) وأعداد الثُقوب(-0.753) . تمَّيز الهجين (P2×P4) بقُدرة خاصَّة معنوية على الائتلاف لصفة الغلَّة الحبيَّة تحت ظروف العَدوى الصناعيَّة (1.149), شدة الضَّرر(0.266). أبدى الهجين (P1×P6) قُدرة خاصَّة مفيدةٍ عاليَّة المعنوية على الائتلاف لصفات عَدد الحُبُوب بالصَّف2.922) ), النسبة المئويَّة لمَوت القمَّة الناميَّة(0.498-), طول النَفق(-3.444), وأعداد الثُقوب(-0.913). كما تميزت الهجن(P5×P3), (P6×P5) بقدرة خاصة عالية المعنوية لصفة الغلة الحبية(1.038) , 0.384)) على التوالي. The study was done at the field research station Sianow of General Commission for Scientific Agricultural Research at Lattakia, to evaluate the susceptibility of 6 strains of maize Zea mays. L, and fifteen maize crosses obtained by half Diallel cross, against under conditions Industrial infection by large corn stem borer , Sesamia cretica Led. The experience was designed at randomized complete blocks (R.C.B.D). Strain IL.257-09)P1( expressed general high capacity to the attributes of Number of kernels per row(3.089), number of holes (-1.261). Strain IL.298-09 (P2) also expressed general high capacity to the attributes of Ear length (0.717), Intensity of damage (-0.432),% of yield loss (-6.022). strain IL.286-09 (P3) general high capacity to the attributes of diameter Ear (0.292), number of rows per ear (2.806). Strains IL.255-09) P4) )0.036( and IL.228-09)P5) (0.969) also expressed general high capacity to the attributes of grain yield. Strain IL.262-09(P6) expressed general high capacity to the attributes of 100- Kernel weight (1.942), infestation grain yield )0.784), tunnel length (-5.629), Percentage of dead hearts (-1.132). Specific Combining Ability had showed significant positive effects: the estimation (P1×P2) expressed high capacity for Percentage of dead hearts )-0.449), Intensity of damage (-0.563(, number of holes (-1.644), ,% of yield loss (2.781). The estimation (P1×P3) expressed high capacity for Ear length (1.368), grain yield (0.050). the estimation (P2×P6) expressed high capacity for Number of rows per Ear(2.550), Percentage of dead hearts (-0.382), number of holes (-0.753). The estimation (P2×P4) expressed high capacity for infestation grain yield (1.149), Intensity of damage (0.266). The estimation (P1×P6) expressed high capacity for Number of kernels per row (2.922), Percentage of dead hearts )-0.498(, tunnel length (-3.444), number of holes (-0.913). The estimations (P3×P5), (P5×P6) expressed high capacity for grain yield (1.038), (0.384).